2010
DOI: 10.4067/s0034-98872010001300004
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between clinical evaluation of liver size versus ultrasonography evaluation according to body mass index (BMI) and biotypes

Abstract: (Rev Med Chile 2010; 138: 1495-1501.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Also, there was no found significant difference between sexes (Babu Naik et al, 2017). Brazilian females and males' same values were 11.9 cm and 11.4 cm, respectively (Silva et al, 2010). The same value was in Malaysian male and female subjects aged between 52.6 years, 12.20 cm and 11.7 cm, respectively (Khammas & Mahmud, 2020) and in Indian healthy subjects, 14.07 cm (Balasubramanian et al, 2016).…”
Section: Discussionmentioning
confidence: 64%
“…Also, there was no found significant difference between sexes (Babu Naik et al, 2017). Brazilian females and males' same values were 11.9 cm and 11.4 cm, respectively (Silva et al, 2010). The same value was in Malaysian male and female subjects aged between 52.6 years, 12.20 cm and 11.7 cm, respectively (Khammas & Mahmud, 2020) and in Indian healthy subjects, 14.07 cm (Balasubramanian et al, 2016).…”
Section: Discussionmentioning
confidence: 64%
“…In 2010 Silva R.M. et al [2] showed that liver measurements obtained by clinical examination correlates well with ultrasound method, but underestimated the actual liver size in adults, which can be demonstrated by the statistically significant difference between the final mean value obtained by clinical observation and that obtained by ultrasound method. A 2013 study of Mouratev et al [3] demonstrated that medical students with less than two hours training http://dx.doi.org/10.35630/2199-885X/2020/10/3.11 could obtain liver size measurements using ultrasound that were more accurate and had less variability than physicians with 10 to 20 years of clinical experience) using physical examination, including palpation, percussion and auscultation scratch techniques.…”
Section: Introductionmentioning
confidence: 99%